Pergerakan Perempuan dalam Memperoleh Kesetaraan Gender dalam Film Moxie: Sebuah Pendekatan Feminis - Alvita, Marsha (EDUJ : English Education Journal, 2023)
This research examines the types of feminism and women's movements in the Moxie (2021) movie that aim to fight the patriarchal system and sexism, and how the main female character and other female characters can deal with it. Moxie (2021) is a coming-of-age genre movie that contains elements of feminism. The data collection used is descriptive qualitative method. The theory of feminism used in this research was the theory of feminism from Tong and Boots (2018). The results of this study show that there were four types of feminism, namely Liberal feminism, Radical feminism, Psychoanalytic and Gender feminism, and Ecofeminist feminism. Then, it was found that there were 4 women's movements that supporting feminism, namely Viviane started zine Moxie as a form of women's resistance, zine Moxie influenced the women's movement in schools, women maintained their self-esteem, and women dared to speak up. Afterwards, some of the moral messages found were the existence of a patriarchal system, discrimination, and sexual harassment until the women dare to fight back and form a feminism club called Moxie. Women deserve to have rights over themselves, such as having equal rights with men, being able to become leaders, and being able to have opinions freely.